2009
DOI: 10.1128/aac.01543-08
|View full text |Cite
|
Sign up to set email alerts
|

Activity Profile In Vitro of Micafungin against Spanish Clinical Isolates of Common and Emerging Species of Yeasts and Molds

Abstract: A collection of 2,278 isolates belonging to 86 different fungal species was tested with micafungin and eight other drugs using the EUCAST procedures. Micafungin was active against species of Candida and Aspergillus (even azole-resistant species) as well as Penicillium spp., Scedosporium apiospermum, and Acremonium spp. It was inactive for species of Basidiomycota and Mucorales and for multiresistant species such as those of Fusarium.Micafungin is a new drug that belongs to the echinocandin class of antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 23 publications
3
24
1
1
Order By: Relevance
“…Muñoz et al identified prior use of antifungal agents (mainly fluconazole) as the only factor that independently predicted the presence of a C. krusei BSI (17). It is worth noting that not all strains of C. glabrata are necessarily resistant to fluconazole and that other species can exhibit fluconazole resistance (2,8). This may explain, at least in part, the different conclusions obtained in our study in comparison with those obtained by previously described approaches.…”
Section: Discussioncontrasting
confidence: 56%
“…Muñoz et al identified prior use of antifungal agents (mainly fluconazole) as the only factor that independently predicted the presence of a C. krusei BSI (17). It is worth noting that not all strains of C. glabrata are necessarily resistant to fluconazole and that other species can exhibit fluconazole resistance (2,8). This may explain, at least in part, the different conclusions obtained in our study in comparison with those obtained by previously described approaches.…”
Section: Discussioncontrasting
confidence: 56%
“…The echinocandins are the newest class of antifungal agents, and recent studies have found favorable results for the use of echinocandins such as micafungin, caspofungin, or aminocandin for the treatment of invasive aspergillosis (145,283,616,617). Indeed, most Aspergillus species tested, with the exception of A. flavus and certain A. nidulans isolates, are susceptible to micafungin (128). The echinocandins act in a fungistatic manner against A. fumigatus, and recently, resistance to the echinocandins has been identified for numerous Aspergillus species.…”
Section: Aspergillus Fumigatus Drug Resistance: the Echinocandinsmentioning
confidence: 99%
“…is not uniform. Several studies have reported that the species of Candida most frequently involved in human infections, Candida albicans, Candida tropicalis, Candida parapsilosis, Candida glabrata, and Candida krusei, usually exhibit low MICs of voriconazole, although the voriconazole MICs for strains with resistance to fluconazole are proportionally higher than are those for fluconazole-susceptible isolates (3)(4)(5)13).…”
mentioning
confidence: 99%